Consumer Perception Towards Adoption of Electric Vehicles: A Literature Review - Khajuria, Vivek; Singh, Harvinder (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The global shift towards sustainable mobility has accelerated interest in electric vehicles (EVs), positioning them as a promising alternative to traditional internal combustion engine vehicles. However, the adoption of EVs is not solely driven by technology and policy but significantly influenced by consumer perception. This review explores the multifaceted nature of consumer attitudes toward EVs, synthesizing insights from behavioural theories and empirical studies across developed and developing countries. Key factors shaping perception include environmental awareness, economic considerations, range anxiety, technological awareness, and social influence. While consumers in developed nations exhibit growing acceptance due to favourable infrastructure and incentives, emerging markets like India face challenges related to affordability, awareness, charging infrastructure and policy clarity. The review also highlights the role of information dissemination, government intervention, and evolving market dynamics in transforming consumer attitudes. Understanding and addressing these perceptual barriers is crucial for accelerating EV adoption globally and in India. Future research should focus on longitudinal studies and real-world user experiences to better predict adoption trends.